Association of different approaches to low level laser therapy in the treatment of surgical dehiscence of knee arthroplasty (Research, Society and Development, 2021)
The objective of this study was to demonstrate the association of photobiomodulation, photodynamic therapy, vacuum laser therapy, blood irradiation with transcutaneous laser and topical Polyhexamethylene Biguanide gel dressing in the treatment of dehiscence in knee arthroplasty. The methodology used was a descriptive case report, with data collection on the patient's treatment through the electronic medical record. The signs and symptoms presented by the patient were analyzed, as well as the characteristics of the wound. Thus, the protocols used were individually prescribed, ensuring differentiated care for the patient. It was authorized by the ethics committee and the patient signed an informed consent form. The results showed that the association of different photobiomodulation approaches were effective in complete wound healing. After 8 days, we observed a decrease in bed depth, erythema and inflammation of the surrounding tissue, with delimitation of the wound edges; as well as skin whitening. As it was a chronic, infected wound, complete healing took place in sixty-three days. It is concluded that the combination of photodynamic action with negative pressure stimulating vascularization and oxygenation, as well as improving body conditions with SVPBM, promoted a much faster recovery than each individual action.